2012
DOI: 10.1016/j.jvs.2011.11.140
|View full text |Cite
|
Sign up to set email alerts
|

Calf muscle oxygen saturation and the effects of supervised exercise training for intermittent claudication

Abstract: Supervised exercise training is not associated with increased gastrocnemius muscle oxygenation during exercise or increased hyperemic hemoglobin flow after a model of ischemia. This suggests that the symptomatic improvement witnessed is not the result of increased oxygen delivery to the active muscle. The enhanced recovery after exercise training therefore reflects a combination of enhanced metabolic economy and increased oxidative capacity, suggesting that exercise training helps reverse an acquired metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 17 publications
(16 reference statements)
7
43
1
2
Order By: Relevance
“…As such, the working muscles require an adequate supply so that O 2 exceeds (or at least matches) demand. As expected, during incremental exercise, we observed a steady decline in SMO 2 % representing an imbalance between supply and utilization [34]. Pertinently, once patients reached a nadir in SMO 2 %, cessation of the test quickly followed due to fatigue and/or inability to keep pace with the test.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As such, the working muscles require an adequate supply so that O 2 exceeds (or at least matches) demand. As expected, during incremental exercise, we observed a steady decline in SMO 2 % representing an imbalance between supply and utilization [34]. Pertinently, once patients reached a nadir in SMO 2 %, cessation of the test quickly followed due to fatigue and/or inability to keep pace with the test.…”
Section: Discussionsupporting
confidence: 76%
“…This minimum value reportedly occurs as maximal aerobic capacity (i.e., VO 2 peak/max) is neared or reached [3537]. This response has been observed in other studies (e.g., [3437, 4648]).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Of note, few therapeutic strategies to date have been shown to effectively improve muscle oxygenation during exercise in patients with IC. For example, Beckitt et al (6) recently reported that angioplasty, but not supervised exercise training, modestly improved gastrocnemius muscle oxygenation during submaximal exercise in claudicants (6). In the present study, we observed that sildenafil reduced ⌬[DeoxyHbϩMb] by ϳ40% relative to the placebo condition during the graded treadmill test (Fig.…”
Section: Effects Of Sildenafil On Muscle Oxygenationsupporting
confidence: 59%
“…An alternative explanation is that the magnitude of the improvement in muscle oxygenation evoked by sildenafil was insufficient to be translated into a measurable change in walking tolerance. However, this seems unlikely as the improvement observed herein is comparable to that achieved after angioplasty (6), which typically enhances walking tolerance in patients with IC (6,62). Lastly, it is worth highlighting that NIRS measurements were performed in a single site in the gastrocnemius muscle, and it is unclear whether the observed local improvement in microvascular O 2 delivery-to-utilization matching after sildenafil extends to the other regions of the muscle, as well as to other muscles in the leg recruited during walking.…”
Section: Effects Of Sildenafil On Muscle Oxygenationmentioning
confidence: 59%